In vivo assessment of the therapeutic effects of lyophilized leech saliva extract from (Huridinaria manillensis) on LNCaP tumor xenograft model in nude mice - Ammar, Amr; Hessein, Mohamed; Guns, Emma; Chin, Mei; Helal Uddin, A.B.M.; Abdualkader, Abdulrahman; Alaama, Mohammed; Merzouk, Ahmed; Ghawi, Abbas; Kucuk, Omer (American Society of Clinical Oncology, 2015)
Background: Ancient traditional physicians from many countries used leeching to treat a wide range of diseases for thousands of years. A large number of peptides and proteins have been identified and characterized in leech saliva extract (LSE), including anti thrombotic agents, cancer metastasis inhibitors and antimicrobials Currently, leech therapy is established as an important tool in microsurgery and reconstructive operations having demonstrated superior clinical outcomes for the optimal salvage of grafted tissues. Methods: In the current study, we have determined the in vivo efficacy of LSE from (Huridinaria manillensis) on castration resistant LNCaP xenograft mouse model. Mice were divided into three groups of six, mice were subcutaneously injected with either LSE (5 mg/kg), docetaxel (10 mg/kg), or vehicle once a week. PSA and tumor volume were measured weekly. After four weeks of treatment, mice were euthanized, tumors and organs were collected for transcriptome and immunohistochemical (IHC) analysis. Results: There was a significant decrease in the tumor volume and PSA with either docetaxel (10mg/kg) or LSE (5 mg/kg) treated groups compared to the control. While there was no significant difference between the antitumor activity of docetaxel (10mg/kg) and LSE (5 mg/kg). IHC showed significant increase in caspase3 and significant decrease in Ki67 and PCNA expression in the LSE treated mice compared to the control group. Interestingly, transcriptome analysis of tumor samples showed that LSE modulated cytokine production, monocyte adhesion, steroidogenesis, and P38 MAPK signaling pathways. Conclusions: LSE has significant antitumor activity in LNCaP tumor xenograft models with no apparent side effects. This can be attributed, at least partly, to its inhibition of cellular proliferation, induction of apoptosis, modulation of immunity and steroidogenesis.